Analisis Praktik Keperawatan Berbasis Bukti Efektivitas Latihan Range Of Motion Aktif Terhadap Pencegahan Kontraktur pada Lansia Pasca Stroke: Evidence-Based Nursing Practice Analysis of the Effectiveness of Active Range of Motion Exercises on Contracture Prevention in Post-Stroke Elderly - Rizky Yanuarika Saputri; Maria Susila Sumartiningsih (MPI Press, 2026)
Background: Stroke is a neurological disease that causes motor impairment, hemiparesis, and immobility in patients, particularly the elderly. This mobility impairment can trigger joint contractures if not properly managed.Objectives: This study aimed to assess the effectiveness of active Range of Motion (ROM) exercises in preventing contractures in post-stroke elderly.Research Methods: This study used an Evidence-Based Nursing (EBN) approach with a quasi-experimental pretest-posttest design. The sample consisted of eight post-stroke elderly, divided into intervention and control groups. The intervention group received regular active ROM exercises, while contracture assessments were conducted before and after the intervention. Statistical analysis was used to assess significant differences between groups.Results: All respondents experienced contractures, with 50% being categorized as mild and 50% as severe. After the intervention, 50% of respondents no longer experienced contractures, 25% remained mild, and 25% remained severe. The mean contracture score decreased from 2.50 to 1.25, with a standard deviation decreasing from 0.577 to 0.500. Intergroup analysis showed a significant difference (p = 0.017; p < 0.05), indicating that active ROM exercises were effective in reducing contracture rates.Conclution: The conclusion of this study is that active ROM exercises are effective in preventing and reducing contractures in post-stroke elderly.